1998
DOI: 10.1016/s0014-5793(98)00165-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of a plant plasma membrane sucrose transporter by phosphorylation

Abstract: The protein phosphatase inhibitor okadaic acid (OA) either provided directly to sugar beet (Beta vulgaris L.) leaf discs or infiltrated in the leaf blade rapidly inhibited sucrose uptake. Methyl okadaic acid, a biologically inactive analogue of OA, had only a marginal effect on uptake. OA inhibited proton-motive force-driven uptake of sucrose into plasma membrane vesicles, without affecting their proton permeability. OA did not significantly affect the amount of sucrose transporters present in the vesicles, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 52 publications
4
46
0
Order By: Relevance
“…Protein phosphorylation is one of the most important and best characterized posttranslational protein modifications regulating cellular signaling processes. In plants, previous work suggested that protein phosphorylation plays a direct role in the regulation of sugar transporter transcription and sugar transport activity (Roblin et al, 1998;Ransom-Hodgkins et al, 2003). Key enzymes from carbon metabolism may also be directly regulated by phosphorylation (Sugden et al, 1999;Ikeda et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphorylation is one of the most important and best characterized posttranslational protein modifications regulating cellular signaling processes. In plants, previous work suggested that protein phosphorylation plays a direct role in the regulation of sugar transporter transcription and sugar transport activity (Roblin et al, 1998;Ransom-Hodgkins et al, 2003). Key enzymes from carbon metabolism may also be directly regulated by phosphorylation (Sugden et al, 1999;Ikeda et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It was then subcloned into the pGEM-T easy vector (Promega, Fitchburg, WI). The EcoRI-SIRK1-SmaI fragment was then cloned into the plant transformation vector pEZR(H)-LN (a kind gift from Staffan Persson Lab, Max Planck Institute for Molecular Plant Physiology) upstream and as a fusion of the GFP coding sequence, resulting in the plasmid 35 S::AtSIRK1-GFP. The construct pGEM-T easy-EcoRI-SIRK1-SmaI was used for mutating Ser-744 of AtSIRK1 to Ala-744 or Asp-744.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the regulation of sucrose metabolism, posttranslational regulation through the phosphorylation of sucrose phosphate synthase has been elucidated (34). Furthermore, there are indications of the regulation of sucrose transport through phosphorylation (35,36), although the precise functions of the phosphorylation events remain to be determined. In the past decade, a number of systematic medium-to large-scale mass-spectrometrybased phosphoproteomics studies have resulted in the identification of protein phosphorylation sites, and the magnitude of phosphorylation in many cases was condition dependent (37)(38)(39)(40)(41)(42).…”
mentioning
confidence: 99%
“…Both proteins colocalize in sieve elements (Kühn et al, 1997;Weise et al, 2000). Localization of SUT1 protein in sieve elements and SUT1 mRNA at the orifices of plasmodesmata interconnecting companion cells and sieve elements, together with the high turnover of both SUT1 mRNA and protein, indicate that trafficking of mRNA or protein occurs from companion cells into enucleate sieve elements by way of plasmodesmata (Kühn et al, 1997).Sugar transport is highly regulated, and sucrose-specific signaling pathways are involved in controlling transport activity (Chiou and Bush, 1998), potentially by using protein phosphorylation (Roblin et al, 1998). Overexpression of pyruvate decarboxylase in potato leads to a 10-fold increase in sugar export, demonstrating the capacity to regulate sugar export from leaves within a wide dynamic range (Tadege et al, 1998).…”
mentioning
confidence: 99%
“…For example, the CCB2 domain contains a serine residue at a highly conserved position, which is predicted to be the target for regulation by phosphorylation by a serine/threonine kinase. Sucrose transport already has been described to be regulated by phosphorylation (Roblin et al, 1998). …”
mentioning
confidence: 99%